Stacey's extraordinary words - Abrams, Stacey; Thomas, Kitt (New York, New York : Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
When she is chosen to compete in the local spelling bee, Stacey learns that, win or lose, her words are powerful, and sometimes perseverance is the most important word of all, in this debut picture book from the iconic voting rights advocate.
Keywords: Spelling bees -- Juvenile fiction; Perseverance (Ethics) -- Juvenile fiction; African American children -- Juvenile fiction; Biographies; Picture books